PENGEMBANGAN MEDIA KOMIK "KERJASAMA DI LINGKUNGANKU" SEBAGAI SARANA INTERNASIONAL NILAI KARAKTER PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Sawal, Bujang; Siregar, Nasyariah; Saputri, Vioni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In order to teach character qualities in fourth-grade children of SDN 008/IX Tanjung on Pancasila Education material with the theme "Cooperation in My Environment," this project attempts to create comedic media. Research and development (R&D) using a 4D development paradigm (Define, Design, Development, Disseminate) is the approach. Three digital platforms NextG Toon Maker, Gemini AI, and Canva were used in the creation process. Nineteen fourth-graders served as the trial subjects. Observation sheets, teacher response questionnaires, and expert validation questionnaires were used as data gathering tools. According to the evaluation of material experts (90%–100%), media experts (87.5%–95%), and language experts (100%), the validation findings indicated that comics fell into the extremely practical category. With a very practical category, the practicality level achieved a percentage of 95.83%. With an average score of 4.00, which falls into the highly effective category, the effectiveness level achieved is 100%. Without the use of technology, this printed comic has demonstrated the ability to help pupils internalize strong character characteristics and translate the abstract idea of ​​mutual cooperation into tangible forms. The study came to the conclusion that the comic medium created is workable, useful, and efficient for use in primary school Pancasila Education instruction.